Between Past and Future - Interviews - Part 1
Correspondent Iván Bedö from Magyar Radio (Hungarian Radio) interviews some of the participants of the international conference "Between Past and Future: The Revolutions of 1989 and the Struggle for Democracy in Central and Eastern Europe" organized by the CEU. Short remarks are provided by Agnes Heller, Richard Holbrook, Vladimir Tismăneanu and Adam Michnik.